KSHV Reprogramming of Host Energy Metabolism for Pathogenesis - Liu, Xiaoqing; Zhu, Caixia; Wang, Yuyan; Wei, Fang; Cai, Qiliang (Frontiers in cellular and infection microbiology, 2021)
Reprogramming of energy metabolism is a key for cancer development. Kaposi’s sarcoma-associated herpesvirus (KSHV), a human oncogenic herpesvirus, is tightly associated with several human malignancies by infecting B-lymphocyte or endothelial cells. Cancer cell energy metabolism is mainly dominated by three pathways of central carbon metabolism, including aerobic glycolysis, glutaminolysis, and fatty acid synthesis. Increasing evidence has shown that KSHV infection can alter central carbon metabolic pathways to produce biomass for viral replication, as well as the survival and proliferation of infected cells. In this review, we summarize recent studies exploring how KSHV manipulates host cell metabolism to promote viral pathogenesis, which provides the potential therapeutic targets and strategies for KSHV-associated cancers.